Factors Related to the Incidence of Hypertension in Bitung City, North Sulawesi Province - Olvi Sukoco; Karel Pandelaki; Greta Jane Pauline Wahongan (Universitas Gorontalo, 2022)
Hypertension is a silent killer which is a factor in the occurrence of non-communicable diseases throughout the world. This has become one of the priority public health problems in Indonesia. This study aimed to determine the risk factors for hypertension > stage 1 in the working area of the Sagerat Health Center, Bitung City, Indonesia. This study used a cross-sectional design. A total of 107 people have agreed to become respondents according to the inclusion and exclusion criteria. Simple random sampling was used to determine the research sample. The results of this study indicate that more than 50% of respondents suffer from hypertension > stage 1. While the chi-square test shows that age, genetic history, obesity, alcohol consumption, and tobacco use have a relationship with the incidence of hypertension > stage 1. The only variable of age did not have a significant relationship. While the results of the binary logistic regression showed that people aged 46 or older, had a hereditary history of hypertension, were obese, consumed alcohol, and smoked had a risk of hypertension > stage 1. Based on the results of this study, it is hoped that the Bitung City government will campaign for a healthy diet such as reducing smoking behavior and alcohol consumption in the community.